Educação não escolar: um estudo sobre as suas expressões pedagógicas e sociais na relação com a escola - Vasconcelos, Ailton Marques de (2015)
This research reports the study on non school educational activities named and identified by some terms: popular education, social education and non-formal education. Furthermore, it analyzes the relationship of this phenomenon with the school. It is empirical research conducted from the collection of information on entities in the State of São Paulo, that develop non school educational programs and projects. Data were obtained through the Internet, in electronic sites of organizations using the technique of content analysis. hypotheses raised: a) the non-school educational activities require didactic and pedagogical grounding and therefore has low capacity to generate learning; b) the non-school education consist is in extreme social control mechanism; c) non-school education is increasingly competing with school. The theoretical referential that guides the research is seated in studies of thinkers of Critical Theory of Society - Theodor W. Adorno, Max Horkheimer, Walter Benjamin and Herbert Marcuse - and the work of Karl Marx and Friedrich Engels. It is verified that the theme in question is vast and complex, as are actions that do not have full legitimacy and for which the various subjects involved attribute different meanings and even contradictory meanings. Finally, the results demonstrate that these actions a large extent express more social control and intensifying processes of pseudoformation